Analisis Kesulitan Belajar Pada Kemampuan Komunikasi Matematis Siswa MTs di Kota Cimahi Dengan Materi Segitiga dan Segiempat - Ucu Nugrawati; Nuryakin Nuryakin; M Afrilianto (Universitas Sarjanawiyata Tamansiswa, 2018)
The role of mathematics is very important in daily life, therefore the subjects of mathematics are taught in every level of education, from kindergarten to college. This study aims is to describe the mathematical communication ability of grade VIII students of MTs Fatahillah which amounts to 30 students in understanding triangular and rectangular materials. Another aims arevto know students learning osbtacle related to communication skills. Instruments of this study are written test. The results of this study is show that the students difficulties are they do not memorize the formula, interpreting solution mistakes because students does not pay attention to questions, and students difficult to understand about the problem that given to them.